Renga, Research, Reflexivity: Poetic Representation. (November 2019) - Lahman, Maria K. E.; Hancock, Emilie; Alhudithi, Ahlam; Kincaid, Tyler; Lafferty, Mel; Patchett, Erin; Loften, Larry; Couch, Connie
In a graduate course dedicated to writing and representing qualitative research in varied ways members challenged themselves to create a renga, a Japanese form of cooperative linked poetry, around the topic of doctoral students' graduate school experiences, employing imagery from natural elements. Along with creating a stanza of the poem each poet wrote a reflection as a way of engaging reflexively with the process. Areas of note included thinking in a new way, finding the way back to a way of thinking, the challenge in creating a poem, and power in the process and ensuing results.